Impact of model training course (MTC) on knowledge gain of extension functionaries about sustainable Rabi oilseed production (Journal of Oilseed Brassica, 2026)
A study was conducted with 20 extension personnel represented Sate Departments of Agriculture from eight states of the country to find out the knowledge gain and opinion of the participants about a model Training Course organized by ICAR, Directorate of Rapeseed-Mustard Research, Bharatpur (Raj) on advances in eco friendly management practices for sustainable Rabi oilseed production. Findings show that the highest mean Per cent Score (MPS) in pre training test obtained by the respondents was 75.0 and lowest MPS was 31.4 with average knowledge score of 40.2 having co-efficient range of 0. 5899. In post test, highest mean per cent score obtained by the respondents was 86.0 and lowest scoring was 57.8 with average knowledge MPS 68.0 and co efficient of range 0.355. The study shows that initial knowledge of the participants was poor having only 40.2 per cent. After the exposure of training a significant improvement found in knowledge of the participants as the pre test scores increased from 40.2 to 68.0 per cent in post test along with 69.15 per cent gain in knowledge. Participants were fully satisfied with the physical arrangements inside the class as well as out of it. They were also of the opinion that the trainers made effective use of important teaching methods appropriate for the transfer of technology. The trainees reported that they had major learning about the agronomic practices of Rabi oilseeds, integrated eco-friendly management of diseases, insects, biogas technology. They also mentioned that they acquired new skills for the farming system, identification of varieties, seed production, hybrid development, identification of major pest and diseases of Rabi oilseeds, etc. The opinion of participants regarding overall grading of training was found excellent.